Traumatic Diaphragmatic Hernia: Anaesthetic Consideration - Khadgaray, Raghu Nandan; Shah, Santosh; Baral, Pawan Puspa (Journal of Universal College of Medical Sciences, 2018)
Any type of trauma may lead to diaphragmatic hernia with blunt forces accounting for majority. Diaphragmatic hernias require a high level of suspicion to detect. Brain, pelvis, long bones, liver, spleen, and aorta are some other organs that can be severely damaged and need different anesthetic management. Gastric decompression, pre-oxygenation, rapid sequence induction and mechanical ventilation with low tidal volume after intubation were used in anesthetic management for thoracotomy and repair. Traumatic diaphragmatic hernia can be life threatening as it may compromise cardiorespiratory function.